Asset Waqf Management Model in the Health Sector LAZNAS Daarut Tauhiid Peduli Surabaya - Basar Dikuraisyin; Ghosyi Harfiah Ningrum; Julianinggar Lusiana Isnaini (AL-FALAH : Journal of Islamic Economics, 2022)
Purpose: Modernization has brought the application of waqf to develop in various parts of the country. The reason is, not only in terms of Islam and worship,waqf has close links with legal, social and economic aspects that are highlighted because waqf assets can produce high-value assets whose results can be used for the welfare of the people.Design/Mothod/Approach : Using a qualitative method with a descriptive approach, this study explains how the pattern of asset waqf management in the form of medical devices was launched in a health program by LAZNAS DT Peduli with program partners, starting from planning activities to the realization steps. The main data were obtained through moderate participation observation techniques and semi-structured interview techniques along with the research sample. The data analysis technique includes three activities; data reduction on the main and important things from the results of observations and interviews, followed by data presentation in the form of narrative descriptions, to drawing conclusions to answer the formulation of the problem.Findings: The results of the study explain that management requires continuity of the process. The dynamics obtained from the beginning to the end must be consistent and consistent with the design they have. LAZNAS DT Peduli as a philanthropic institution in waqf management with an innovation model makes initial planning the decisive stage.Originality/Values: Followed by structuring action steps that are packaged in the organizing stage, followed by action steps or realization in order to get results to support the medical device waqf program until supervision of sterilizers has been carried out at the same time to ensure the benefits of medical device waqf are well conveyed.